This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: as exponential Stop Start SX = 0 SY = 0 SXY = 0 SX2 = 0 For X = 1 To N, Step 1 SX = SX + Xd(X) SY = SY + Yd(X) SXY = SXY + Xd(X) * Yd(X) SX2 = SX2 + Xd(X) ^ 2 SY2 = SY2 + Yd(X) ^ 2 Next X M = (N * SXY - SX * SY) / (N * SX2 - SX ^ 2) B = (SY - M * SX) / N F = (N * SXY) - (SX * SY) D = (N * SX2) - (SX) ^ 2 E = (N * SY2) - (SY) ^ 2 R = F / (Sqr(D) * Sqr(E)) Stop...
View Full Document
This note was uploaded on 09/18/2011 for the course ENGR 160 taught by Professor Sengupta during the Fall '07 term at Iowa State.
- Fall '07